The Effect of E-LKPD Liveworksheet-Assisted Problem-Based Learning Models on the Critical Thinking Skills of Students in Grade V - Sari, Adelia Putri; Sulistyowati, Prihatin; Sakdiyah, Siti Halimatus (Sistem-Among : Jurnal Pendidikan Sekolah Dasar, 2025)
Critical thinking skills are essential competencies for students. However, elementary school students in Indonesia still show weaknesses in this aspect, as they tend to emphasize memorization. This study aims to examine the effect of the E-LKPD Liveworksheet-assisted Problem-Based Learning (PBL) model on the critical thinking skills of fifth-grade students in Natural and Social Sciences (IPAS). The study uses a quantitative approach with a quasi-experimental design of the Pretest-Posttest Nonequivalent Control Group Design. The research subjects involved 58 students from two elementary schools in Pamekasan Regency, divided into an experimental group and a control group. The instrument was a multiple-choice critical thinking test consisting of 10 items that had been validated and proven reliable. The data were analyzed using normality, homogeneity, N-Gain, and independent t-tests with the help of SPSS 22. The results showed that the experimental group obtained higher post-test scores (M = 77.86) and N-Gain (0.6179, medium-high category) compared to the control group (M = 55.67; N-Gain = 0.3513, medium category), with a significant difference (p < 0.05). These findings confirm that integrating PBL with E-LKPD  Liveworksheet effectively improves critical thinking skills. The novelty of this study lies in the integration of PBL with interactive digital worksheets in elementary school science education. It contributes theoretically to the study of digital-based PBL and provides practical benefits for teachers in designing innovative, student-centered learning in the digital age.